Wage System Given By Plantation Lords to Contract Coolie Workers In East Sumatra - Riskita*, Ayu Novia; Putri, Lia Agustia; Muris, Dwiki Pamungkas; Wahyuni Solin, Sri Ganti; Riski Malau, Brata Eka (Universitas Syiah Kuala, 2023)
This study tries to find out the wage system that coolies obey in tobacco plantations in Deli, East Sumatra, the methods used by the authorities to punish coolies there, and the influence of the wage system on the colonial life of coolies in tobacco plantations in Deli. East Sumatra. using research techniques and libraries to obtain the necessary facts (library research). The research findings indicate that Development has emerged as a key attraction for other parties wishing to make financial investments in Deli. The gardeners' piece rate scheme is used only for their benefit. The coolies actually suffered a lot under this regime because their 35 cents per hour work was too little to meet their needs. Another problem is if the garden owner withholds wages when the employees are disciplined and pays for tools that the employees will use at work according to the wage system. The porter was responsible for paying for everything in bulk. This causes the life of the coolies to become even more difficult, because for their daily needs they have to toil with lives that are threatened.